2004
DOI: 10.1002/jat.984
|View full text |Cite
|
Sign up to set email alerts
|

Components of diesel exhaust particles differentially affect lung expression of cyclooxygenase‐2 related to bacterial endotoxin

Abstract: We have reported previously that components of diesel exhaust particles (DEP) differently affect acute lung injury related to lipopolysaccharide (LPS) in mice. This study examined the effects of components of DEP on the lung expression of cyclooxygenase (COX)-1 and -2 in the presence or absence of LPS. ICR mice were divided into six experimental groups that received vehicle, LPS (2.5 mg kg(-1)), organic chemicals in DEP (DEP-OC) extracted with dichloromethane (4 mg kg(-1)), residual carbonaceous nuclei after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
0
10
1
1
Order By: Relevance
“…The current findings are consistent with these prior reports and establish the importance of the NF-B/ COX-2 signaling pathway during RANKL induction in FLS. While it has recently been shown that silica particles induce COX-2 in fibroblasts (8,17,35), the current studies are the first to implicate a calpain-dependent mechanism.…”
Section: Discussionmentioning
confidence: 86%
“…The current findings are consistent with these prior reports and establish the importance of the NF-B/ COX-2 signaling pathway during RANKL induction in FLS. While it has recently been shown that silica particles induce COX-2 in fibroblasts (8,17,35), the current studies are the first to implicate a calpain-dependent mechanism.…”
Section: Discussionmentioning
confidence: 86%
“…In order to elucidate which components of the organic DEP fraction was responsible for inflammatory responses, different extracts have been analyzed (i.e., primarily those drawn into methanol [Inoue et al, 1997] or dichloromethane [Inoue et al, 2004]). Other Investigators have used a benzene extract containing about 82% of all the B[a]P in DEP to study its effect on IL-8 secretion by epithelial cells (Kawasaki et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Feeding trials were conducted to investigate the effects of 9c,11t-CLA and 10t,12c-CLA isomers on COX-2 protein expression and PGE 2 release in vivo. Mouse lung was selected based on known COX-2 expression and PGE 2 release from this organ after inflammatory stimulation (18,(38)(39)(40). As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%